Visualization and Concept Drift Detection Using Explanations of Incremental Models - Demšar, Jaka; Bosnić, Zoran; Kononenko, Igor (Informatica, 2014)
The temporal dimension that is ever more prevalent in data makes data stream mining (incremental learning)an important field of machine learning. In addition to accurate predictions, explanations of the modelsand examples are a crucial component as they provide insight into model's decision and lessen its black boxnature, thus increasing the user's trust. Proper visual representation of data is also very relevant to user'sunderstanding – visualization is often utilised in machine learning since it shifts the balance between perceptionand cognition to take fuller advantage of the brain's abilities. In this paper we review visualisationin incremental setting and devise an improved version of an existing visualisation of explanations of incrementalmodels. Additionally, we discuss the detection of concept drift in data streams and experiment witha novel detection method that uses the stream of model's explanations to determine the places of change inthe data domain.